TRILOGI FILOSOFIS KENTONGAN BANYUMASAN: ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI DALAM GELIAT TRADISI SENI LOKAL - Zaki Zulfian; Ryolita, Widya Putri (Studi Budaya Nusantara, 2024)
This study aims to analyze the philosophical dimensions of Kentongan art in Banyumas, covering ontology, epistemology, and axiology. This research employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. Primary data were obtained by visiting the Kentongan Bambu Laras community in Patikraja Village, Patikraja District, Banyumas Regency. Indepth interviews were conducted with Mr. Sujiono, the leader of the Kentongan Bambu Laras community, as the primaryinformant. The results show that Kentongan art in Banyumas has undergone significant development, both in terms of musical instruments and its functions. Initially, Kentongan only used a single bamboo instrument and served as a traditional communication tool. However, over time, it has evolved into a performing art involving various musical instruments and functions as a medium of entertainment for the community. This development is closely tied to the role of the Banyumas government, which has provided attention and support to this art form as one of the region's cultural attractions. Through the study of ontology, epistemology, and axiology, this research reveals that Kentongan art not only possesses aesthetic value but also embodies profound philosophical values as part of the cultural identity of the Banyumas community.